2012
DOI: 10.18832/kp2012002
|View full text |Cite
|
Sign up to set email alerts
|

Non-volatile N-nitrosamines in brewing industry. Part 1. - Arrising and methods of estimation.

Abstract: Na rozdíl od N-nitrosaminů těkavých je toho v pivovarství o nitrosaminech netěkavých, jejich hlavních představitelích a mechanismech vzniku, známo velmi málo.V první části publikace věnované problematice netěkavých nitrosaminů jsou proto podány základní informace týkající se jejich výskytu, mechanismu vzniku a metod stanovení v pivu a ostatních potravinách. Contrary to volatile N-nitrosamines, about representatives and mechanism of arrising of non-volatile nitrosamines in brewing industry is known only a littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
1
5
0
1
Order By: Relevance
“…The recommended but not legislatively supported limit is 20 μg(NNO)/L, and 51% of tested samples (97 counts from 191) did not meet this recommendation. 10,11 Exceeding ATNC concentrations still occur frequently in commercial beers, which supports this study's importance in revealing unknown representatives of others, especially nonvolatile NOCs.…”
Section: Gc-ms/mssupporting
confidence: 79%
See 4 more Smart Citations
“…The recommended but not legislatively supported limit is 20 μg(NNO)/L, and 51% of tested samples (97 counts from 191) did not meet this recommendation. 10,11 Exceeding ATNC concentrations still occur frequently in commercial beers, which supports this study's importance in revealing unknown representatives of others, especially nonvolatile NOCs.…”
Section: Gc-ms/mssupporting
confidence: 79%
“…For instance, earlier studies found NPRO in levels between <1−11 μg/L (median 8 μg/L, 13 beer samples) or within the range <1−6 μg/L (average 1.7 μg/L, 28 beer samples). 10,12 Regarding 4cyanophenol and 4-nitrosophenol, they ranged between <1− 15 μg/L (median of <1 μg/L) and 2−138 μg/L (median of 8 μg/L), respectively. Since these compounds were not found in beer yet, no data to compare estimated levels were available.…”
Section: Gc-ms/msmentioning
confidence: 99%
See 3 more Smart Citations